Integrating fragment-based screening with targeted protein degradation and genetic rescue to explore eIF4E function - Swee Y. Sharp; Marianna Martella; Sabrina D’Agostino; Christopher I. Milton; George Ward; Andrew J. Woodhead; Caroline J. Richardson; Maria G. Carr; Elisabetta Chiarparin; Benjamin D. Cons; Joseph Coyle; Charlotte E. East; et al. (Nature Communications)
Abstract Eukaryotic initiation factor 4E (eIF4E) serves as a regulatory hub for oncogene-driven protein synthesis and is considered a promising anticancer target. Here we screen a fragment library against eIF4E and identify a ligand-binding site with previously unknown function. Follow-up structure-based design yields a low nM tool compound (4, Kd = 0.09 µM; LE 0.38), which disrupts the eIF4E:eIF4G interaction, inhibits translation in cell lysates, and demonstrates target engagement with eIF4E in intact cells (EC50 = 2 µM). By coupling targeted protein degradation with genetic rescue using eIF4E mutants, we show that disruption of both the canonical eIF4G and non-canonical binding sites is likely required to drive a strong cellular effect. This work highlights the power of fragment-based drug discovery to identify pockets in difficult-to-drug proteins and how this approach can be combined with genetic characterization and degrader technology to probe protein function in complex biological systems.